International financial reporting and analysis - Alexander, David (Thomson Learning, 2005)
This book is overdue. With the decision taken by the European Union (EU) to require all listed EU companies to prepare their consolidated accounts in accordance with International Accounting Standards (IAS) from 2005 onwards, there is a pressing need to train people in the financial reporting language of the future. New is not so much that new standards are replacing old standards